Implementation of K-Means Clustering to Human Development Indicators in East Nusa Tenggara - Simarmata, Justin Eduardo; Chrisinta, Debora; Purnomo, Miko (Journal of Research in Mathematics Trends and Technology, 2024)
K-Means has been adopted to group various cases related to the quality of humanresources and economic growth. This study aims to apply K-Means to thecharacteristics based on selected Human Development Index (HDI) indicators,namely the average length of schooling, the expectation of length of schooling andlife expectancy in Province of East Nusa Tenggara. The optimal cluster obtainedis 6 clusters. The cluster with the highest average value of all variables is in cluster1 which is Kupang City area. Meanwhile, condition cluster 6 provides the smallestlife expectancy value compared to other clusters. The smallest average variable ofschool length is in cluster 2. The regions that provide the smallest numberexpectation of length of schooling is in cluster 5.